2020
DOI: 10.1002/mgg3.1401
|View full text |Cite
|
Sign up to set email alerts
|

MYT1 role in the microtia‐craniofacial microsomia spectrum

Abstract: Craniofacial microsomia (CFM, OMIM: 164210), also known as the oculo-auriculo-vertebral spectrum, hemifacial microsomia, or Goldenhar syndrome, is typically characterized by uni-or bilateral microtia and mandibular hypoplasia in addition to ocular, vertebral, and renal abnormalities (Gorlin, Cohen, & Hennekam, 2001; Heike & Hing, 2009). CFM, like other complex diseases, usually occurs sporadically. In multiplex families, the transmission is usually autosomal dominant, often with incomplete penetrance, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Epibulbar dermoids also appear to be a specific clinical feature of OAVS that could compensate the absence of ear anomaly if HFM is present. Some authors recently suggested as OAVS diagnostic criteria the presence of two phenotypic findings including epibulbar dermoids such as mandibular hypoplasia and epibulbar dermoids, or preauricular tag and epibulbar dermoid or lateral oral cleft and epibulbar dermoids 25…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Epibulbar dermoids also appear to be a specific clinical feature of OAVS that could compensate the absence of ear anomaly if HFM is present. Some authors recently suggested as OAVS diagnostic criteria the presence of two phenotypic findings including epibulbar dermoids such as mandibular hypoplasia and epibulbar dermoids, or preauricular tag and epibulbar dermoid or lateral oral cleft and epibulbar dermoids 25…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
“…Lateral oral cleft, also named macrostomia, was also proposed to be one of the two minimal clinical features by Luquetti et al , associated with either mandibular hypoplasia or preauricular tag 25…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Variants in transcription factors involved in neural crest cell migration and patterning (TFAP2A, SIX1, SIX5, EYA1, HOXA10, HOXA2), chromatin modifiers (CHD7, KMT2D, KDM6A), growth factors and their receptors (GDF6, FGF3, FGF10, FGFR2, FGFR3), DNA pre-replication complexes (ORC1, ORC4, ORC6, CDC6, CDT1), ribosome assembly (TCOF1, POL1RC, POL1RD), and the spliceosome (EFTUD2, TXNL4A, SF3B4) have been implicated in monogenic syndromes that include malformation of the ears or mandible 7 . Variants in MYT1 have been identified in unrelated individuals with CFM, suggesting a possible role in disease pathogenesis 8,9 . The two largest families described in the literature to date demonstrating dominant inheritance of CFM identified linkage of the trait to chromosomal bands 11q12-13 and 14q32; however, the responsible gene within each linkage interval was not identified at the time of study 10,11 .…”
mentioning
confidence: 99%